Correlation between serum caspase-3 with clinical and laboratory manifestation of SLE - Z. Omran, Tuqa; E. Al-araji, Amna; W. Mohammed Ali, Shawqi; M. Jabbar, Sawsan; N. Al-Fatlawi, Sabah (International Journal of Psychosocial Rehabilitation, 2020)
Background: SLE is a multisystem disease that is due to dysregulation of immune system and apoptosis process. Caspase-3 is one of the important enzymes in the apoptotic pathways. In this study we try to assess correlation between serum levels of this enzyme with some clinical and laboratory manifestations of SLE. Methods: we have enrolled 50 patients with SLE and measured their serum caspase-3 levels end have recorded some of the clinical and laboratory manifestation. Then we correlate these with corresponding serum caspase-3 levels. Results and conclusions: only Serum creatinine showed significant correlation with serum caspase-3 level